Vascular Smooth Muscle Cells: A Therapeutic Target in Atherosclerosis - Lingna Zhao; Li Zhao; Deshen Liu; Fangze Huang; Qinbao Peng; Jun Lu; Jiaguo Zhou; Shaoyi Zheng; Xiu Liu (Reviews in Cardiovascular Medicine, 2025)
Background: Vascular smooth muscle cells (VSMCs) are involved in atherosclerotic plaque development. The formation of VSMC-originated foam cells, phenotypic switching, and VSMC proliferation, migration, apoptosis, and autophagy play different roles in atherosclerosis (AS). Main Body: Foam cell formation promotes the generation and evolution of atherosclerotic plaques. The VSMC phenotype, switching from contractile to other forms, is important in the formation and progression of AS. VSMC proliferation, migration, and apoptosis affect the stability of atherosclerotic plaques through the fibrous cap. VSMC proliferation and migration can increase the thickness of the fibrous cap of the plaques, which protects plaques from rupture and is beneficial for slowing the occurrence of advanced lesions. However, apoptosis can accelerate plaque rupturing and trigger severe cardiovascular disease. The autophagy of VSMCs has a protective influence on safeguarding cellular homeostasis in the early stages of AS. However, increased autophagy of VSMCs in the late stages of AS can lead to cell death, thereby affecting the stability of late-stage plaques. This review comprehensively reviews recent research on genetic proteins and mechanisms influencing various aspects of VSMCs, including VSMC-derived foam cells, phenotypic switching, proliferation, migration, apoptosis, and autophagy. Additionally, this review aimed to examine the implications of VSMCs for AS and discussed several regulators that can impact the progression of this condition. Our review thoroughly summarizes the latest research developments in this field. Conclusion: Based on the vital role of VSMCs in AS, this review provides an overview of the latest factors and mechanisms based on VSMC-derived foam cells, phenotype switching, proliferation, migration, apoptosis, and autophagy. The review also introduces certain regulators that can inhibit the development of AS. An understanding of the role of VSMCs aids in identifying new targets and directions for advancing innovative anti-atherosclerotic therapeutic regimens and provides new insights into the development of treatments for AS.